Antibacterial activity of Ethanol Extract of Purple Passion Fruit Peel (Passiflora edulis Sims) on Staphylococcus aureus and Escherichia coli - Eka Nugraha, Sony; Achmad, Suryadi; Sitompul, Erly (Indonesian Journal of Pharmaceutical and Clinical Research, 2018)
Abstract.North Sumatera is the central production of purple passion fruit in Indonesia. Passion fruit was processing into beverage product that produced passion fruit peel waste. The passion fruit peel has potential effect as a sources of medicine which is need to be examined such as its antibacterial effect. The purpose of this study was to determine the characterization of simplicia, phytochemical screening and antibacterial activity of ethanol extract of purple passion fruit peel against Staphylococcus aureus and Escherichia coli. The simplicia powder was examined its characteristic include water content, water soluble extract, ethanol soluble extract, total ash and acid insoluble ash assay. The extraction was process by percolation method using ethanol 96% , then tested antibacterial activity against Staphylococcus aureus and Escherichia coli using agar diffusion method with paper discs.The result showed that the simplicia characteristic of passion fruit peel were water content of 8.64%, water soluble extract of 31.69%, ethanol soluble extract of 13.02%, ash total of 7.89%, and insoluble ash in acid of 0.816%. The phytochemical screening simplicia and ethanol extract showed the presence of flavonoid, glycoside, saponin, tannin and steroid/triterpenoid.The antibacterial activity test showed that the ethanol extract has an effective inhibition at the concentration of 300 mg/ml against Staphylococcus aureus and Escherichia coli, it showed dose dependent manner. Keywords: Passiflora edulis Sims, antibacterial, passion fruit peel, Staphylococcus aureus and Escherichia coli